Misyar Marriage: A Comparative Legal Analysis of Yusuf al-Qaradawi and ‘Abd al-‘Aziz ibn ‘Abd Allah ibn Baz’s Thought - Awal, Muhammad Yaumil; Rahman, Sarman (MAQASIDI: Jurnal Syariah dan Hukum, 2025)
This study examines the opinions of several contemporary scholars regarding the practice of misyar marriage, which represents a relatively new issue within the discourse of Islamic law. Fundamentally, marriage is a sacred bond established between a husband and wife through the fulfillment of mutual rights and obligations as a marital partnership. This research employs a library-based research method, collecting data in the form of scholarly opinions on the practice of misyar marriage. The data sources are derived from various books and academic journals related to the Misyar marriage. The findings of this study suggest that the issue of misyar marriage presents a contemporary legal challenge among modern scholars, as it is not explicitly addressed in the works of classical jurists. This condition has prompted scholars of the mutaʾakhkhirīn period to conduct extensive analyses to address issues related to the practice of misyar marriage. Following an examination of these scholarly analyses, the author finds a fundamental divergence of opinion regarding the legal validity of misyar marriage. Among these views, Yusuf al-Qaradawi permits misyar marriage unconditionally, whereas ʿAbd al-ʿAziz ibn ʿAbd Allah ibn Baz permits it subject to certain conditions.